1142 The neural basis of impaired self-awareness after traumatic brain injury. Issue 3 (9th February 2012) - Ham, T; Bonnelle, V; Barber, T; Leech, R; Kinnunen, K; De Boissezon, X; Greenwood, R; Sharp, D J
Abstract : Traumatic brain injury (TBI) often impairs self-awareness, which limits recovery and rehabilitation. The neural basis for this is unclear. Impaired self-awareness can be studied by identifying patients who inconsistently monitor their actions. We used functional and structural imaging to investigate: (1) whether patients with impaired performance monitoring appropriately activate attentional and error processing networks; and (2) whether impaired performance monitoring is associated with disconnection in distributed brain networks. Methods: We studied a group of 49 TBI patients with either normal or impaired performance monitoring. We used fMRI to assess the neural response to salient events on the stopsignal task. We then used DTI and volume-based morphometry to study group differences in grey and white matter. Results: All groups performed the task accurately. Patients with impaired performance monitoring had significantly less activation of the right lateralized fronto-parietal attentional network. All groups activated the core error network equally. DTI analysis showed more white matter disruption in impaired patients. Resting state analysis showed lower functional connectivity in the attentional and error processing networks in the impaired group. Conclusion: Impaired performance monitoring was associated with a behavioural profile indicating broad attention deficits. Consistent with this, the impaired group showed lower activation within a right lateralized attention network but normal activation of the error network. Functional connectivity was reduced within both networks, likely the result of disconnection of distributed brain networks due to diffuse axonal injury.